Reconstructing Environmental Criminal Law in Indonesia Through a Comparative Zemiological Legal Study - Fernando, Zico Junius; Sueni, Annisa Sabilla; Arifin, Firdaus; Ramadhani, Susi; Zulaika, Almira Novia (Faculty of Law Universitas Trunojoyo Madura, 2026)
Environmental crimes in Indonesia are increasingly recognized not only as violations of legal norms but also as social and ecological harms affecting communities and ecosystems. However, the existing framework of environmental criminal law remains largely formalistic, emphasizing administrative violations and statutory illegality while insufficiently addressing the broader dimension of socio-ecological harm. This research examines how a zemiological perspective can contribute to the reconstruction of environmental criminal law in Indonesia through a comparative legal study. Using a normative juridical method with statute, conceptual, and comparative approaches, this study analyzes Indonesian environmental criminal law alongside developments in Belgium, the European Union, Argentina, Scotland, and the Philippines. The findings demonstrate that Indonesian law continues to rely on formal legality and weak corporate accountability, whereas comparative jurisdictions increasingly recognize severe environmental harm, ecocide, and collective victimization as bases for criminal responsibility. The contribution of this research lies in three main aspects. First, it develops a zemiological framework as a new theoretical basis for evaluating environmental criminal law beyond formal statutory violations, emphasizing social and ecological harm as the central criterion for criminalization. Second, it provides a systematic comparative legal analysis that identifies normative gaps between Indonesian law and emerging global models of harm-based environmental criminal law. Third, it proposes a conceptual model for reconstructing environmental criminal law in Indonesia by integrating the principles of social harm, the recognition of ecocide, and strengthened corporate liability.